Isolation, characterization and biological activity of acidic phospholipase A(2) isoforms from Bothrops jararacussu snake venom - Ketelhut, DFJ; de Mello, M. H.; Veronese, ELG; Esmeraldino, L. E.; Murakami, M. T.; Arni, R. K.; Giglio, JR; Cintra, ACO; Sampaio, S. V. (Elsevier B.V., 2003)
Acidic phospholipase A(2) (PLA(2)) isoforms in snake venoms, particularly those from Bothrops jararacussu, have not been characterized. This article reports the isolation and partial biochemical, functional and structural characterization of four acidic PLA(2)s (designated SIIISPIIA, SIIISPIIB, SIIISPIIIA and SIIISPIIIB) from this venom. The single chain purified proteins contained 122 amino acid residues and seven disulfide bonds with approximate molecular masses of 15 kDa and isoelectric points of 5.3. The respective N-terminal sequences were: SIIISPIIA-SLWQFGKMIDYVMGEEGAKS; SIIISPIIB-SLWQFGKMIFYTGKNEPVLS; SIIISPIIIA-SLWQFGKMILYVMGGEGVKQ and SIIISPIIIB-SLWQFGKMIFYEMTGEGVL. Crystals of the acidic protein SIIISPIIIB diffracted beyond 1.8 Angstrom resolution. These crystals are monoclinic with unit cell dimensions of a = 40.1 Angstrom, b = 54.2 Angstrom and c = 90.7 Angstrom. The crystal structure has been refined to a crystallographic residual of 16.1% (R-free = 22.9%). Specific catalytic activity (U/mg) of the isolated acidic PLA(2)s were SIIISPIIA = 290.3 U/mg; SIIISPIIB = 279.0 U/mg; SIIISPIIIA = 270.7 U/mg and SIIISPIIIB = 96.5 U/mg. Although their myotoxic activity was low, SIIISPIIA, SIIISPIIIB and SIIISPIIIA showed significant anticoagulant activity. However, there was no indirect hemolytic activity. SIIISPIIIB revealed no anticoagulant, but presented indirect hemolytic activity. With the exception of SIIISPIIIB, which inhibited platelet aggregation, all the others were capable of inducing time-independent edema. Chemical modification with 4-bromophenacyl bromide did not inhibit the induction of edema, but did suppress other activities. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: acidic PLA(2)s; Bothrops jararacussu; N-terminal sequence; platelet aggregation inhibition; X-ray crystallography